On the collection of marine crabs (Decapoda: Brachyura) in the Zoological Survey of India, Western Regional Centre, Pune, with a note on the taxonomy of Sphaerozius scaber (Fabricius, 1798) (Menippidae) - Pati, S.k.; Sujila, P.s.; Ng, Peter K.l. (Zootaxa, 2022)
The Zoological Survey of India, Western Regional Centre, Pune (ZSI-WRC) contains 1887 specimens of mostly unstudied marine brachyuran crabs. The present systematic study on the marine crabs of ZSI-WRC reports 62 species in 44 genera, 18 families and nine superfamilies. Of these, four genera and 13 species are new distributional records within India. We also record three species for the first time from the Indian waters: Metopograpsus cannicci Innocenti, Schubart & Fratini, 2020 (Grapsidae MacLeay, 1838), Varuna yui Hwang & Takeda, 1986 (Varunidae H. Milne Edwards, 1853), and Ilyograpsus paludicola (Rathbun, 1909) (Macrophthalmidae Dana, 1851). The record of Varuna yui is significant as it is the first time it has been found from the western Indian Ocean. The subfamily Ilyograpsinae Števčić, 2005, has likewise not previously been reported from India. The taxonomy of the poorly known menippid crab, Sphaerozius scaber (Fabricius, 1798), is clarified with the designation of a lectotype, and its taxonomy is discussed. Sphaerozius scaber can be distinguished from the only congener S. nitidus Stimpson, 1858, by its prominently tuberculated carapace, palm and carpus of the chelipeds, and the strongly curved male first gonopod, with the distal part gently tapering into a truncate tip. Sphaerozius scaber is a new addition to the west coast of India. With the inclusion of the present new records, India is now known to have 939 species of marine brachyuran crabs in 375 genera of 63 families.